2.3.12 first order ode clairaut

Table 2.419: first order ode clairaut

#

ODE

CAS classification

Solved?

169

\[ {}y = y^{\prime } x -\frac {{y^{\prime }}^{2}}{4} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

1536

\[ {}y^{\prime } = -\frac {x}{2}-1+\frac {\sqrt {x^{2}+4 x +4 y}}{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

3325

\[ {}y = y^{\prime } x +{y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

3326

\[ {}y = y^{\prime } x +\frac {1}{y^{\prime }} \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

3327

\[ {}y = y^{\prime } x -\sqrt {y^{\prime }} \]

[[_homogeneous, ‘class G‘], _Clairaut]

3328

\[ {}y = y^{\prime } x +\ln \left (y^{\prime }\right ) \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

3329

\[ {}y = y^{\prime } x +\frac {3}{{y^{\prime }}^{2}} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

3330

\[ {}y = y^{\prime } x -{y^{\prime }}^{{2}/{3}} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

3331

\[ {}y = y^{\prime } x +{\mathrm e}^{y^{\prime }} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

3332

\[ {}\left (y-y^{\prime } x \right )^{2} = {y^{\prime }}^{2}+1 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

3333

\[ {}x {y^{\prime }}^{2}-y y^{\prime }-2 = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

4088

\[ {}\left (y-y^{\prime } x \right )^{2} = {y^{\prime }}^{2}+1 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

4383

\[ {}x {y^{\prime }}^{3}-y {y^{\prime }}^{2}+1 = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

4384

\[ {}y = y^{\prime } x +{y^{\prime }}^{3} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

4388

\[ {}2 {y^{\prime }}^{2} \left (y-y^{\prime } x \right ) = 1 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5365

\[ {}{y^{\prime }}^{2}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5366

\[ {}{y^{\prime }}^{2}-y^{\prime } x +y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5369

\[ {}{y^{\prime }}^{2}+\left (1-x \right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5370

\[ {}{y^{\prime }}^{2}-\left (x +1\right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5371

\[ {}{y^{\prime }}^{2}-\left (2-x \right ) y^{\prime }+1-y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5372

\[ {}{y^{\prime }}^{2}+\left (x +a \right ) y^{\prime }-y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5377

\[ {}{y^{\prime }}^{2}-2 y^{\prime } x +2 y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5381

\[ {}{y^{\prime }}^{2}-4 \left (x +1\right ) y^{\prime }+4 y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5383

\[ {}{y^{\prime }}^{2}-a x y^{\prime }+a y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5385

\[ {}{y^{\prime }}^{2}+\left (b x +a \right ) y^{\prime }+c = b y \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5415

\[ {}2 {y^{\prime }}^{2}-\left (1-x \right ) y^{\prime }-y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5437

\[ {}x {y^{\prime }}^{2}-y y^{\prime }+a = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

5442

\[ {}x {y^{\prime }}^{2}+\left (a -y\right ) y^{\prime }+b = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

5443

\[ {}x {y^{\prime }}^{2}+\left (x -y\right ) y^{\prime }+1-y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

5444

\[ {}x {y^{\prime }}^{2}+\left (a +x -y\right ) y^{\prime }-y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

5458

\[ {}\left (x +1\right ) {y^{\prime }}^{2}-\left (x +y\right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

5459

\[ {}\left (a -x \right ) {y^{\prime }}^{2}+y y^{\prime }-b = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

5462

\[ {}\left (3 x +1\right ) {y^{\prime }}^{2}-3 \left (y+2\right ) y^{\prime }+9 = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5480

\[ {}x^{2} {y^{\prime }}^{2}-\left (2 x y+1\right ) y^{\prime }+1+y^{2} = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

5481

\[ {}x^{2} {y^{\prime }}^{2}-\left (a +2 x y\right ) y^{\prime }+y^{2} = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

5502

\[ {}\left (a^{2}+x^{2}\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+b +y^{2} = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

5599

\[ {}{y^{\prime }}^{3}+a x y^{\prime }-a y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5600

\[ {}{y^{\prime }}^{3}-\left (b x +a \right ) y^{\prime }+b y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5608

\[ {}{y^{\prime }}^{3}-{y^{\prime }}^{2}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5623

\[ {}x {y^{\prime }}^{3}-y {y^{\prime }}^{2}+a = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5629

\[ {}x^{2} {y^{\prime }}^{3}-2 x y {y^{\prime }}^{2}+y^{2} y^{\prime }+1 = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5660

\[ {}2 \sqrt {a y^{\prime }}+y^{\prime } x -y = 0 \]

[[_homogeneous, ‘class G‘], _Clairaut]

5666

\[ {}\sqrt {a^{2}+b^{2} {y^{\prime }}^{2}}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5667

\[ {}a \sqrt {{y^{\prime }}^{2}+1}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5670

\[ {}a \left (1+{y^{\prime }}^{3}\right )^{{1}/{3}}+y^{\prime } x -y = 0 \]

[_Clairaut]

5671

\[ {}\cos \left (y^{\prime }\right )+y^{\prime } x = y \]

[_Clairaut]

5676

\[ {}\left ({y^{\prime }}^{2}+1\right ) \sin \left (-y+y^{\prime } x \right )^{2} = 1 \]

[_Clairaut]

5680

\[ {}\ln \left (y^{\prime }\right )+y^{\prime } x +a = y \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5683

\[ {}\ln \left (y^{\prime }\right )+a \left (-y+y^{\prime } x \right ) = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5686

\[ {}y^{\prime } \ln \left (y^{\prime }\right )-\left (x +1\right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5687

\[ {}y^{\prime } \ln \left (y^{\prime }+\sqrt {a +{y^{\prime }}^{2}}\right )-\sqrt {{y^{\prime }}^{2}+1}-y^{\prime } x +y = 0 \]

[_Clairaut]

5697

\[ {}y = y^{\prime } x +\frac {a y^{\prime }}{\sqrt {{y^{\prime }}^{2}+1}} \]

[_Clairaut]

5761

\[ {}y = y^{\prime } x +y^{\prime }-{y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

5762

\[ {}y = y^{\prime } x +\sqrt {b^{2}-a^{2} {y^{\prime }}^{2}} \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

6571

\[ {}y = y^{\prime } x +{y^{\prime }}^{4} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

6672

\[ {}{y^{\prime }}^{2}-y^{\prime } x +y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

6674

\[ {}x {y^{\prime }}^{5}-y {y^{\prime }}^{4}+\left (x^{2}+1\right ) {y^{\prime }}^{3}-2 x y {y^{\prime }}^{2}+\left (x +y^{2}\right ) y^{\prime }-y = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

6681

\[ {}y = y^{\prime } x -2 {y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

8457

\[ {}{y^{\prime }}^{2}-y^{\prime } x +y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

8466

\[ {}{y^{\prime }}^{2}-y^{\prime } x +y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

8467

\[ {}y = y^{\prime } x +k {y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

8472

\[ {}x {y^{\prime }}^{2}+\left (x -y\right ) y^{\prime }+1-y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

8473

\[ {}y^{\prime } \left (y^{\prime } x -y+k \right )+a = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

8477

\[ {}x {y^{\prime }}^{3}-y {y^{\prime }}^{2}+1 = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

8543

\[ {}x^{2} {y^{\prime }}^{3}-2 x y {y^{\prime }}^{2}+y^{2} y^{\prime }+1 = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

8548

\[ {}x^{2} {y^{\prime }}^{2}-\left (2 x y+1\right ) y^{\prime }+1+y^{2} = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

8551

\[ {}\left (y^{\prime }+1\right )^{2} \left (y-y^{\prime } x \right ) = 1 \]

[[_1st_order, _with_linear_symmetries], _dAlembert]

8552

\[ {}{y^{\prime }}^{3}-{y^{\prime }}^{2}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

8555

\[ {}x {y^{\prime }}^{2}+\left (k -x -y\right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

8729

\[ {}\frac {{y^{\prime }}^{2}}{4}-y^{\prime } x +y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

8747

\[ {}x f^{\prime }-f = \frac {{f^{\prime }}^{2} \left (1-{f^{\prime }}^{\lambda }\right )^{2}}{\lambda ^{2}} \]

[_Clairaut]

10390

\[ {}{y^{\prime }}^{2}+\left (x -2\right ) y^{\prime }-y+1 = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10391

\[ {}{y^{\prime }}^{2}+\left (x +a \right ) y^{\prime }-y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10392

\[ {}{y^{\prime }}^{2}-\left (x +1\right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10397

\[ {}{y^{\prime }}^{2}+\left (a x +b \right ) y^{\prime }-a y+c = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10411

\[ {}2 {y^{\prime }}^{2}+\left (x -1\right ) y^{\prime }-y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10429

\[ {}x {y^{\prime }}^{2}-y y^{\prime }+a = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

10437

\[ {}\left (x +1\right ) {y^{\prime }}^{2}-\left (x +y\right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

10438

\[ {}\left (3 x +1\right ) {y^{\prime }}^{2}-3 \left (y+2\right ) y^{\prime }+9 = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10439

\[ {}\left (3 x +5\right ) {y^{\prime }}^{2}-\left (3 y+x \right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

10440

\[ {}a x {y^{\prime }}^{2}+\left (b x -a y+c \right ) y^{\prime }-b y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

10441

\[ {}a x {y^{\prime }}^{2}-\left (a y+b x -a -b \right ) y^{\prime }+b y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

10449

\[ {}x^{2} {y^{\prime }}^{2}-\left (a +2 x y\right ) y^{\prime }+y^{2} = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

10457

\[ {}\left (x^{2}+1\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2}-1 = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

10462

\[ {}\left (x^{2}+a \right ) {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2}+b = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

10532

\[ {}{y^{\prime }}^{3}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10533

\[ {}{y^{\prime }}^{3}-\left (x +5\right ) y^{\prime }+y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10544

\[ {}x {y^{\prime }}^{3}-y {y^{\prime }}^{2}+a = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10566

\[ {}\sqrt {{y^{\prime }}^{2}+1}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

10575

\[ {}\ln \left (y^{\prime }\right )+a \left (-y+y^{\prime } x \right ) = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

10580

\[ {}\left ({y^{\prime }}^{2}+1\right ) \sin \left (-y+y^{\prime } x \right )^{2}-1 = 0 \]

[_Clairaut]

12892

\[ {}\left (-y+y^{\prime } x \right )^{2} = {y^{\prime }}^{2}+1 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

12902

\[ {}y y^{\prime } = \left (x -b \right ) {y^{\prime }}^{2}+a \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

12908

\[ {}\left (x^{2}+1\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2}-1 = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

12912

\[ {}y = y^{\prime } x +\frac {1}{y^{\prime }} \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

12914

\[ {}x^{2} {y^{\prime }}^{2}-2 \left (x y-2\right ) y^{\prime }+y^{2} = 0 \]

[[_homogeneous, ‘class G‘], _Clairaut]

13880

\[ {}y = y^{\prime } x +{y^{\prime }}^{2} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Clairaut]

13881

\[ {}y = y^{\prime } x +{y^{\prime }}^{2} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Clairaut]

13897

\[ {}{y^{\prime }}^{2}+\left (x +a \right ) y^{\prime }-y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

14155

\[ {}{y^{\prime }}^{2}-y^{\prime }-y^{\prime } x +y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

14220

\[ {}y = y^{\prime } x +\sqrt {1-{y^{\prime }}^{2}} \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

14222

\[ {}y = y^{\prime } x +\frac {1}{y^{\prime }} \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

14223

\[ {}y = y^{\prime } x -\frac {1}{{y^{\prime }}^{2}} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

14396

\[ {}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Clairaut]

14475

\[ {}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Clairaut]

14476

\[ {}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Clairaut]

14477

\[ {}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Clairaut]

14478

\[ {}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Clairaut]

14479

\[ {}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Clairaut]

15137

\[ {}y^{\prime }+2 x = 2 \sqrt {y+x^{2}} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16125

\[ {}t y^{\prime }-{y^{\prime }}^{3} = y \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16126

\[ {}t y^{\prime }-y-2 \left (t y^{\prime }-y\right )^{2} = y^{\prime }+1 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

16127

\[ {}t y^{\prime }-y-1 = {y^{\prime }}^{2}-y^{\prime } \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16128

\[ {}1+y-t y^{\prime } = \ln \left (y^{\prime }\right ) \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16129

\[ {}1-2 t y^{\prime }+2 y = \frac {1}{{y^{\prime }}^{2}} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16162

\[ {}y = t y^{\prime }+3 {y^{\prime }}^{4} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16164

\[ {}y-t y^{\prime } = -2 {y^{\prime }}^{3} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16165

\[ {}y-t y^{\prime } = -4 {y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16843

\[ {}y = y^{\prime } x +\frac {a}{{y^{\prime }}^{2}} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16844

\[ {}y = y^{\prime } x +{y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16845

\[ {}x {y^{\prime }}^{2}-y y^{\prime }-y^{\prime }+1 = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

16846

\[ {}y = y^{\prime } x +a \sqrt {{y^{\prime }}^{2}+1} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

16847

\[ {}x = \frac {y}{y^{\prime }}+\frac {1}{{y^{\prime }}^{2}} \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

16866

\[ {}y = y^{\prime } x +\sqrt {a^{2} {y^{\prime }}^{2}+b^{2}} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

17385

\[ {}y^{\prime } = -\frac {t}{2}+\frac {\sqrt {t^{2}+4 y}}{2} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Clairaut]

17951

\[ {}y = y^{\prime } x +y^{\prime }-{y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

17953

\[ {}{y^{\prime }}^{2} \left (x^{2}-1\right )-2 x y y^{\prime }+y^{2}-1 = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

17960

\[ {}y^{\prime } = -x +\sqrt {x^{2}+2 y} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

17961

\[ {}y^{\prime } = -x -\sqrt {x^{2}+2 y} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

18601

\[ {}y = y^{\prime } x +y^{\prime }-{y^{\prime }}^{3} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

18708

\[ {}y = y^{\prime } x -{y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

18723

\[ {}{y^{\prime }}^{2}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

18819

\[ {}y = y^{\prime } x +\arcsin \left (y^{\prime }\right ) \]

[_Clairaut]

18824

\[ {}y = y^{\prime } \left (x -b \right )+\frac {a}{y^{\prime }} \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

18846

\[ {}y = y^{\prime } x +\frac {m}{y^{\prime }} \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

18848

\[ {}y = y^{\prime } x +a \sqrt {{y^{\prime }}^{2}+1} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

18849

\[ {}{y^{\prime }}^{2}+y^{\prime } x -y = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

18859

\[ {}y^{2}-2 x y y^{\prime }+{y^{\prime }}^{2} \left (x^{2}-1\right ) = m^{2} \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

18860

\[ {}y = y^{\prime } x +\sqrt {b^{2}+a^{2} y^{\prime }} \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

18861

\[ {}y = y^{\prime } x -{y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

18865

\[ {}{y^{\prime }}^{2} \left (-a^{2}+x^{2}\right )-2 x y y^{\prime }+y^{2}-b^{2} = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

19245

\[ {}y = y^{\prime } x +\frac {a}{y^{\prime }} \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

19246

\[ {}y = y^{\prime } x +y^{\prime }-{y^{\prime }}^{3} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

19247

\[ {}y = y^{\prime } x +a y^{\prime } \left (1-y^{\prime }\right ) \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

19248

\[ {}y = y^{\prime } x +\sqrt {{y^{\prime }}^{2}+1} \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

19249

\[ {}y = y^{\prime } x +\sqrt {b^{2}-a^{2} {y^{\prime }}^{2}} \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

19250

\[ {}\left (y-y^{\prime } x \right ) \left (y^{\prime }-1\right ) = y^{\prime } \]

[[_1st_order, _with_linear_symmetries], _rational, _dAlembert]

19251

\[ {}x {y^{\prime }}^{2}-y y^{\prime }+a = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Clairaut]

19252

\[ {}y = y^{\prime } \left (x -b \right )+\frac {a}{y^{\prime }} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

19253

\[ {}y = y^{\prime } x +{y^{\prime }}^{3} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

19269

\[ {}{y^{\prime }}^{2} \left (-a^{2}+x^{2}\right )-2 x y y^{\prime }+y^{2}+a^{4} = 0 \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

19278

\[ {}\left (x^{2}+1\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2} = 1 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

19284

\[ {}y^{2}-2 x y y^{\prime }+{y^{\prime }}^{2} \left (x^{2}-1\right ) = m \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

19285

\[ {}y = y^{\prime } x -{y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _Clairaut]

19306

\[ {}\left (a^{2}-x^{2}\right ) {y^{\prime }}^{2}+2 x y y^{\prime }+b^{2}-y^{2} = 0 \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]